Copepod Resources In The Selected Inland Water Bodies Of Kerala and Culture Of A Species As Live Feed - Resmi,S (School Of Fisheries Resource Management And Harvest Technology,KUFOS, 2014)
Abstract- Collections for the taxonomic studies were taken from 26 stations in Kerala and 21 species have been collected and identified up to the species level. Two species are described as – Elaphoidella keralaense sp. nov. and Microcyclops indicus sp. nov. The genus Elaphoidella is reporting for the first time from Kerala. Microcyclops rubellus is reporting for first time from India. Ten species are new records from Kerala and the remaining are collected from new distributional areas. Species recorded here comes under 3 orders out of 10 orders reported so far. All species are described with full illustrations.